Classification of KIT/PDGFRA wild-type gastrointestinal stromal tumors: implications for therapy. Issue 6 (June 2015) - Huss, Sebastian; Elges, Sandra; Trautmann, Marcel; Sperveslage, Jan; Hartmann, Wolfgang; Wardelmann, Eva
<x xml:space="preserve">Abstract</x> Gastrointestinal stromal tumors (GIST) are driven mostly by oncogenic KIT or PDGFRA mutations. However, in 10–15% of all GIST, no such activating mutations can be found and these tumors are classified as 'wild-type GIST' (KIT/PDGFRA wt-GIST). Subgroups of KIT/PDGFRA wt-GIST are driven by other sporadic mutations involving the RAS/RAF/MAP-kinase pathway, such as BRAF or KRAS mutations. Furthermore, KIT/PDGFRA wt-GIST are observed in the context of hereditary syndromes, such as neurofibromatosis Type 1, in which the lack of neurofibromin 1 also leads to the activation of the RAS/RAF/MAP-kinase pathway. Finally, the deficiency succinate dehydrogenase seems to play a major role in KIT/PDGFRA wt-GIST. In conclusion, KIT/PDGFRA wt-GIST belong to different subgroups defined by diverse underlying genetic alterations leading to different biological phenotypes. The vast majority of KIT/PDGFRA wt-GIST will not respond to imatinib. Further research to unravel the pathogenesis of KIT/PDGFRA wt-GIST is prerequisite to the development of effective treatment strategies.